Social distancing predicts suicide rates: Analysis of the 1918 flu pandemic in 43 large cities, research note. Issue 5 (9th February 2021) - Stack, Steven; Rockett, Ian R. H.
Abstract: Social distancing (e.g., school and business closings) has been emphasized in current sociopolitical efforts in controlling COVID‐19. Such policies are assumed to increase suicide risk through lowering social integration. While two studies have linked the presence of a pandemic to suicide rates, no study has assessed the degree of social distancing on suicide rates during a pandemic. The present study fills this gap with data on the extent of social distancing during the Spanish flu epidemic in 43 large cities. The results find that increasing social distancing increases suicide rates independent of the influenza mortality rate.